An Analysis of International Military Health Systems Using the Military Medical Corps Worldwide Almanac. Issue 9 (28th August 2021) - Leone, Ryan M; Homan, Zenobia; Lelong, Antonin; Bandekow, Lutz; Bricknell, Martin
ABSTRACT: Introduction: A number of organizations publish comparisons of civilian health systems between countries. However, the authors were unable to find a global, systematic, and contemporary analysis of military healthcare systems. Although many databases exist for comparing national healthcare systems, the only such compilation of information for military medical systems is the Military Medical Almanac. A thorough review of the Almanac was conducted to understand the quality of information provided in each country's profile and to develop a framework for comparing between countries. This information is valuable because it can facilitate collaboration and lesson sharing between nations while providing a structured source of information about a nation's military medical capabilities for internal use. Materials and Methods: Each of the 142 profiles (submitted by 132 countries) published in the Almanac were reviewed. The information provided was extracted and aggregated into a spreadsheet that covered the broader categories of country background, force demographics, beneficiary populations, administration and oversight, physical structures and capabilities, research capabilities, and culture and artifacts. An initial sample of 20 countries was evaluated to test these categories and their subsections before the rest of the submissions were reviewed. Clear definitions were revised and established for each of the 69 subcategories. Qualitative and quantitative data were compiled in the spreadsheet to enable comparisons between entries. Results: Significant variation was found in how information was presented in country profiles and to what extent this was comparable between submissions. The most consistently provided information was in the country background, where the categories ranged from 90.15% to 100% completion across submissions. There was inconsistency in reporting of the numbers and types of healthcare workers employed within military medical services. Nearly 25% of nations reported providing medical care to family members of service members, but retirees, veterans, reservists, and law enforcement personnel were also mentioned. Some countries described organizational structures, military medical education institutions, and humanitarian operations. A few reported military medical research capabilities, though each research domain was present in 25% or less of all submissions. Interestingly, cultural identities such as emblems were present in nearly 90% of profiles, with many countries also having badges, symbols, and mottos. Conclusions: The Military Medical Almanac is potentially a highly valuable collection of publicly available baseline information on military medical services across the world. However, the quality of this collection is highly dependent on the submission provided by each country. It is recommended that the template for collecting information on each health system be refined, alongside an effort to increase awareness of the value of the Almanac as an opportunity to raise the international profile of each country's military medical system. This will ensure that the Almanac can better serve the international military medical community.